The Global Brain Health Survey: Development of a Multi-Language Survey of Public Views on Brain Health - Budin-Ljøsne, Isabelle; Friedman, Barbara Bodorkos; Suri, Sana; Solé-Padullés, Cristina; Düzel, Sandra; Drevon, Christian A.; Baaré, William F. C.; Mowinckel, Athanasia Monika; Zsoldos, Enikő; Madsen, Kathrine Skak; Carver, Rebecca Bruu; Ghisletta, Paolo; et al. (Frontiers in Public Health, 2020)
Background: Brain health is a multi-faceted concept used to describe brain physiology, cognitive function, mental health and well-being. Diseases of the brain account for one third of the global burden of disease and are becoming more prevalent as populations age. Diet, social interaction as well as physical and cognitive activity are lifestyle factors that can potentially influence facets of brain health. Yet, there is limited knowledge about the population’s awareness of brain health and willingness to change lifestyle to maintain a healthy brain. This paper introduces the Global Brain Health Survey protocol, designed to assess people’s perceptions of brain health and factors influencing brain health. Methods: The Global Brain Health Survey is an anonymous online questionnaire available in 14 languages to anyone above the age of 18 years. Questions focus on 1) willingness and motivation to maintain or improve brain health, 2) interest in learning more about individual brain health using standardized tests, and 3) interest in receiving individualized support to take care of own brain health. The survey questions were developed based on results from a qualitative interview study investigating brain health perceptions among participants in brain research studies. The survey includes 28 questions and takes 15-20 minutes to complete. Participants provide electronically informed consent prior to participation. The current survey wave was launched on June 4, 2019 and will be open until August 31, 2020. We will provide descriptive statistics of samples distributions including follow-up analyses of differences as a function of age, gender, education, country of residence, and we will examine associations between items. The survey is led by the European Union funded Lifebrain project in collaboration with the national brain councils in Norway, Germany, and Belgium, the Brain Foundation Netherlands, and the National University of Ostroh Academy in Ukraine. Discussion: Results from this survey will provide new insights in peoples’ views on brain health, in particular, the extent to which the adoption of positive behaviours can be encouraged. The results will contribute to the development of policy recommendations for supporting population brain health, including measures tailored to individual needs, knowledge, motivations and life situations.